Derivatives and economic growth: links and evidence the impact of the financial derivatives on the real economy - Lema, Diego (2020)
This paper studies the links between the development of derivative markets and economic growth. By acknowledging the shortness of samples hindering any robust econometric analysis, it sets out and empirically checks those links, adopting statistical correlation techniques. It uses developed and emerging economy data over the most extensive period possible and tests for the presence of a structural break after the 2008-2009 crisis. The general result is that derivatives are positively correlated with economic growth, in particular, through the investment and international trade links. Another general result is that there is a concave relationship between growth and derivatives in the case of developed countries.